Association of proton pump inhibitors with gastric and colorectal cancer risk: A systematic review and meta-analysis - Guo, Huizhu; Zhang, Ruiqiu; Zhang, Pei; Chen, Zhaoyang; Hua, Yuqing; Huang, Xin; Li, Xiao (Frontiers in Pharmacology, 2023)
Background: Proton pump inhibitors (PPI) are generally considered to be one of the well-established prescription drug classes and are commonly used to treat most acid-related diseases. However, a growing body of literature showing an association between gastric and colorectal cancer risk and PPI use continues to raise concerns about the safety of PPI use. Therefore, we aimed to investigate the association between proton pump inhibitor use and risk of gastric and colorectal cancer. Methods: We collected relevant articles using PubMed, Embase, Web of Science and Cochrane library from January 1,1990 to March 21,2022. The pooled effect sizes were calculated based on the random-effects model. The study was registered with PROSPERO (CRD42022351332). Results: A total of 24 studies (n = 8,066,349) were included in the final analysis in the screening articles. Compared with non-PPI users, PPI users had a significantly higher risk of gastric cancer (RR=1.82, 95% CI: 1.46-2.29), but not colorectal cancer (RR=1.22, 95% CI: 0.95-1.55). Subgroup analysis showed that there was a significant positive correlation between the use of PPI and the risk of non-cardiac cancer (RR=2.75, 95% CI: 2.09-3.62). There was a significant trend between the duration dependent effect of PPI use and the risk of gastric cancer (<1 year RR=1.56, 95% CI: 1.30-1.86; 1-3 years RR=1.75, 95% CI: 1.28-2.37; >3 years RR=2.32, 95% CI: 1.15-4.66), but not colorectal cancer (≤1 year RR=1.00, 95% CI: 0.78-1.28; >1 year RR=1.18, 95% CI: 0.91-1.54; ≥5 years RR=1.06, 95% CI: 0.95-1.17). Conclusion: We found that PPI use increased gastric cancer risk, but not colorectal cancer risk. This result may be biased due to confounding factors. More prospective studies are needed to further validate and support our findings.